Recent Trends of Microbiota-Based Microbial Metabolites Metabolism in Liver Disease - Ganesan, Raja; Jeong, Jin-Ju; Kim, Dong Joon; Suk, Ki Tae (Frontiers in Medicine, 2022)
Gut-microbiome and microbial metabolomics influence in liver diseases, diagnosis, prognosis, and treatment have been still disputed. The research studies have provocatively claimed that gut-microbiome, metabolomics understanding, and microbial metabolites screening were key for liver cancer and their diseases. An advance of logical innovations in metabolomics profiling, the metabolome inclusion, troubles, and reproducibility of the investigations on every stage are devoted to this domain to link the little atoms in multipart liver diseases such as fatty liver, hepatitis, and cirrhosis. Here, we are not promptly recognizable because of the huge underlying and synthetic variety present inside the liver cellular metabolome. The review focuses on the microenvironmental metabolic stimuli on gut-liver axis. The microbial small-molecules profiling (i.e., semiquantitative monitoring, metabolic discrimination, target profiling, and untargeted profiling) in biological fluids have been completely addressed. Here, we have revised that the differential expression of metabolome of short chain fatty acids (SCFAs), tryptophane, one-carbon metabolisms and bile acid with gut microbiota effects are summarized and discussed. We further present proof-of evidence for gut-microbiota- based metabolomics that manipulate the host’s gut or liver microbes, mechanosensitive metabolites reactions and potential metabolic pathways. We conclude with a forward-looking prospective on future attention in “dark matter” of gut-microbiota and microbial metabolomics.